Business process reengineering role in electronic government - Martín, Rodrigo L. (2006)
Business Process Reengineering (BPR) came up as a key concept in the 1990s, with a high impact on management and transactions of private companies. However, it has not been so well accepted in public administration. Nowadays, many projects for changes in government are related to electronic government. According to this, this article discusses the role of BPR in this context, its contribution to this kind of initiative, and if it is a required element to go forward. Also, the difficulties in carrying out the BPR in the particular case of e-government are analyzed, taking into account the characteristics of this kind of project, the stages that are generally involved and the environment in which it is performed. Finally, a basic structure for the development of egovernment is provided, specifying the insertion of BPR for reaching a more efficient, effective and foreseeable management of new projects.